2018
DOI: 10.1002/ange.201710377
|View full text |Cite
|
Sign up to set email alerts
|

Steigerung der Katalysatoreffizienz in der C‐H‐Aktivierungskatalyse

Abstract: Nur wenige Katalysatoren erreichen hohe Umsatzzahlen in Reaktionen zur Aktivierung von C‐H‐Bindungen. Stattdessen werden üblicherweise 10 Mol‐% eines Katalysators in solchen Reaktionen eingesetzt. Wir geben eine repräsentative Übersicht über effiziente Katalysatornutzung in der C‐H‐Aktivierung, um diesem vernachlässigten Aspekt der Katalyseforschung mehr Aufmerksamkeit zukommen zu lassen und zukünftige Entwicklungen noch effizienterer C‐H‐Aktivierungen zu inspirieren. Wir zeigen Beispiele aus der Palladiumkata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(6 citation statements)
references
References 150 publications
0
6
0
Order By: Relevance
“…over the past two decades as an increasingly important synthetic tool. [1] In particular,transition metal (TM) catalyzed C À Hf unctionalization has witnessed continuing improvements in performance, [2] allowing expansion of the toolbox available for organic material synthesis, [3] natural products synthesis, [4] and drug-discovery programs. [5] In spite of this success,t here is still an eed for the development of C À H transformations that can efficiently operate under mild reaction conditions with broad functional-group tolerance and high selectivity.T he recent enthusiasm for visible light driven reactions has resulted in ar ise in the number of innovative catalytic systems that enable CÀHtransformations under mild reaction conditions.…”
Section: Thedirectfunctionalizationofinertcàhbondshasemergedmentioning
confidence: 99%
“…over the past two decades as an increasingly important synthetic tool. [1] In particular,transition metal (TM) catalyzed C À Hf unctionalization has witnessed continuing improvements in performance, [2] allowing expansion of the toolbox available for organic material synthesis, [3] natural products synthesis, [4] and drug-discovery programs. [5] In spite of this success,t here is still an eed for the development of C À H transformations that can efficiently operate under mild reaction conditions with broad functional-group tolerance and high selectivity.T he recent enthusiasm for visible light driven reactions has resulted in ar ise in the number of innovative catalytic systems that enable CÀHtransformations under mild reaction conditions.…”
Section: Thedirectfunctionalizationofinertcàhbondshasemergedmentioning
confidence: 99%
“…The expansion of the scope using different aliphatic alcohols as substrates was systematically performed comparing results obtained with modified and commercial ruthenium catalysts. No significant difference was observed in the case of diol 2, contrary to alcohols (3)(4)(5) where deuterium uptake occurred with a higher regioselectivity using IAd(0.1 equiv)@Ru/C. The regioselectivity of the deuterium incorporation first determined by the analysis of 1 H NMR spectrum, was then confirmed using 2 H-{ 1 H} 1D NMR spectroscopy @14.1 T (see SI), evidencing the substantial enhancement of regioselectivity afforded by the presence of NHCs at the surface of the Ru catalyst.…”
mentioning
confidence: 72%
“…This fact is probably due to the challenge related to the modulation of heterogeneous catalyst reactivity by organic ligands. [3] In contrast, for other types of important chemical reactions such as hydrogenations, the addition of ligands to influence the reactivity of heterogeneous catalysts has been known for decades. [4] In spite of the fact that N-heterocyclic carbenes (NHCs) are widely applied as ligands in homogeneous catalysis, [5] only recently, Glorius et al reported their capability to tune the reactivity and selectivity of a heterogeneous Ru catalyst (Ru/K-Al 2 O 3 ).…”
mentioning
confidence: 99%
“…The direct functionalization of inert C−H bonds has emerged over the past two decades as an increasingly important synthetic tool . In particular, transition metal (TM) catalyzed C−H functionalization has witnessed continuing improvements in performance, allowing expansion of the toolbox available for organic material synthesis, natural products synthesis, and drug‐discovery programs . In spite of this success, there is still a need for the development of C−H transformations that can efficiently operate under mild reaction conditions with broad functional‐group tolerance and high selectivity.…”
Section: Figurementioning
confidence: 99%
“…over the past two decades as an increasingly important synthetic tool. [1] In particular,transition metal (TM) catalyzed C À Hf unctionalization has witnessed continuing improvements in performance, [2] allowing expansion of the toolbox available for organic material synthesis, [3] natural products synthesis, [4] and drug-discovery programs. [5] In spite of this success,t here is still an eed for the development of C À H transformations that can efficiently operate under mild reaction conditions with broad functional-group tolerance and high selectivity.T he recent enthusiasm for visible light driven reactions has resulted in ar ise in the number of innovative catalytic systems that enable CÀHtransformations under mild reaction conditions.…”
Section: Thedirectfunctionalizationofinertcàhbondshasemergedmentioning
confidence: 99%